Kedudukan Pendidikan Islam dalam Sistem Pendidikan Nasional - Nasimuddin, Nasimuddin; Hasani, Moh. Zaen; Muhammad, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Islamic education holds a significant position within a nation's national education system. This article aims to explore the position of Islamic education within the national education system context using the literature review method. Data were obtained through literature searches from various reliable sources such as scholarly journals, textbooks, and relevant official publications. Data analysis was conducted by identifying and summarizing the main findings from literature relevant to the topic. The results indicate that Islamic education has a significant impact on shaping the character, morality, and religious identity of students. Values such as justice, tolerance, and compassion taught in Islamic education play a key role in building a civilized and sustainable society. The implications of this literature review underscore the importance of strengthening the role of Islamic education in supporting national educational goals and ensuring the integration of Islamic values into educational curricula. Furthermore, the literature also highlights the need for intercultural and interreligious dialogue encouraged by Islamic education to create a more inclusive and harmonious society. This research contributes to expanding understanding of the importance of Islamic education within the national education system and highlights the challenges and opportunities in implementing Islamic values in the context of modern education.